Documentar gráficamente para la memoria - Montañez, Clara M. (2018)
In the field of Heritage and its conservation, drawing accentuates the communicational value that is its own. The graphic documentation is a useful tool for the preservation of cultural values. It represents the architectural good in its entirety, and in the future, it can become a historical document, a graphic testimony of the culture that generates it. San Juan, is a province hit by earthquakes periodically; therefore we need the heritage graphical documentation to assure the transmission of the cultural legacy to the future.